A systematic literature review of mathematics learning media and its contributions - Umi Hanifah; Dyah Worowirastri Ekowati; Dian Fitri Nur Aini (Research and Development in Education (RaDEn), 2024)
A systematic literature review (SLR) aimed to define the trends and advances in mathematical semiotic reasoning research that have been published in journals with a scopus index, as well as their possibilities. Upon selecting the keyword "learning media" from the liquefaction menu within the scopus database, 213 articles were discovered. Moreover, a total of 18 articles satisfied the requirements for analysis. The PRISMA model is used for inclusion and exclusion. The trend of learning media has increased sharply in 2019-2023 by 15 articles (83.33%). The most dominant research type is the quantitative approach (6 articles). According to the author's nationality and international collaboration, Indonesia has the most authors (9, or 42.85%) of any country. Furthermore, the authors of learning media publications are dominated by the Asian continent 11 authors (52.38%). 8 articles carried out national and international collaborations (53.33%). Regarding keywords from 18 articles, there are opportunities in the future to research related to media learning with numbers, media learning and statistics, media learning with arithmetic, and so on. In addition, the contribution of learning media research in mathematics is in the form of contributions to learning planning, the development of mathematics learning media in other scientific fields, and the implementation of learning.